Cartographic images of Slovenia through time - Primož Gašperič (Acta Geographica Slovenica, 2007)
The territory of Slovenia appears on Europe’s oldest maps. Slovenia’s location at the junction of different natural and geographical units and various political formations influenced its traffic and border situation. As a result, for many centuries the territory of Slovenia appeared inaccurately on maps and as part of foreign national units. With the development of cartographical skills and the recognition of cartography in our area in the 16th century and especially from the 17th century on, Slovene territory was depicted equally on maps of the times through the efforts of Slovene and foreign individuals. At first, maps of individual Slovene regions dominated, but from the middle of the 19th century there are more frequent depictions of the entire Slovene territory. Cartographical work thus also became a means of expressing national demands and hopes.